Ready to use therapeutical beverages: focus on functional beverages containing probiotics, prebiotics and synbiotics - Nazhand, Amirhossein (2020)
The growing global interest in functional foods containing nutrients capable of adding possible beneficial health effects is rapidly increasing both interest and consumer demand. In particular, functionalized beverages for their potential positive effect on health e.g., decreasing cholesterol level, lowering sugar, high fiber content, ability to enhance the immune system, and help digestion, have recently received special attention. Among the different beverages available on the market, probiotic dairy and non-dairy products have attracted much attention because of their affordable cost and their numerous therapeutic activities. Fermented milk and yogurt are currently worth €46 billion, with 77% of the market reported in Europe, North America, and Asia. Consumption of dairy beverages has some limitations due for example to lactose intolerance and allergy to milk proteins, thereby leading consumers to use non-dairy beverages such as fruit, grains, and vegetable juices to add probiotics to diet as well as driving the manufacturers to food matrices-based beverages containing probiotic cultures. The purpose of this review article is to evaluate the therapeutic performance and properties of dairy and non-dairy beverages in terms of probiotic, prebiotic, and synbiotic activities.